CATARACT SURGERIES BY PHACO-SANDWICH TECHNIQUE THROUGH SCLEROCORNEAL TUNNEL, A COHORT STUDY IN OMAN - Sadiq, Mohammad Naqaish; Pai, Anant; Kurup, Padma Mohan.J. (Journal of Ayub Medical College Abbottabad, 2006)
Background: To evaluate the changes in Preoperative and Postoperative keratometry results and rapid visual rehabilitation in Cataract surgery by our phaco-sandwich technique through the self sealing sclero-corneal tunnel incision without phacoemulsification. Methods: 96 eyes of 88 patients with age-related cataracts underwent small incision suture less cataract surgery without phacoemulsification. All eyes were operated by the phaco-sandwich technique through sclerocorneal tunnel with 6 mm frown-shaped external scleral incision. 6 mm single piece PMMA lens was implanted in the capsular bag. Patients were evaluated at 1week, 4 weeks and 12 weeks post-operatively. Results: Ninety six eyes of eighty eight patients were our cohort. During the first post-operative week 8 eyes (8.3%) had uncorrected visual acuity (UCVA) of 6/6. By the end of 12 post-operative weeks, 33 eyes(34.5%) had UCVA of 6/6. 64 (66.7%), 72(75%) and 80(83.3%) eyes had best correctable visual acuity (BCVA) of 6/6 after 4 weeks, 8 weeks and 12 weeks respectively. 64 (66.7%) eyes after 4 weeks, 72 (75%) after 8 weeks and 80 (83%) after 12 weeks had best correctable visual acuity (BCVA) of 6/6. Conclusion: Suture less, small-incision cataract surgery is an economical, safe and effective method of managing cataract cases. This technique also ensures satisfactory and rapid rehabilitation for patients. This procedure can be effectively applied to clear the backlog of cataract-related blindness in places wherein the resources for phaco facilities are not available. Keywords : Small incision cataract surgery, Phacoemulsification, Phacosandwich